2011
DOI: 10.1194/jlr.m011569
|View full text |Cite
|
Sign up to set email alerts
|

Human LDL core cholesterol ester packing: three-dimensional image reconstruction and SAXS simulation studies

Abstract: This article is available online at http://www.jlr.org accumulate in the circulation as a result of a defi ciency in the LDL receptor, for example, the LDL can be oxidized and subsequentially interacts with macrophages. The accumulation of cholesterol ester transforms the macrophage into an atherogenic foam cell and contributes to the pathophysiology of atherosclerosis ( 6 ).Previous studies have shown that the cholesterol ester in the core of the LDL particle can exist in two phases accompanying change in tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…It has been shown that the physical state of core lipids changes within milliseconds [44]. This fast kinetics has caused experimental difficulties for long time, however, a recent experimental approach by speeding up freezing allowed to trap the lipids in the molten state [45]. The authors report on a co-existing phase of layered and broken shells for LDL particles, which are shock-frozen in a state above the phase transition.…”
Section: Core Lipid Packing and Lipid Phase Transitionmentioning
confidence: 99%
“…It has been shown that the physical state of core lipids changes within milliseconds [44]. This fast kinetics has caused experimental difficulties for long time, however, a recent experimental approach by speeding up freezing allowed to trap the lipids in the molten state [45]. The authors report on a co-existing phase of layered and broken shells for LDL particles, which are shock-frozen in a state above the phase transition.…”
Section: Core Lipid Packing and Lipid Phase Transitionmentioning
confidence: 99%
“…In comparison to studies based on other methodologies ( 8,9,14,15 ), cryo-EM and image reconstruction have more advantages in preserving the LDL particle in the native state, and intuitively reveal the density distribution of the LDL structure in three-dimensional (3D) images (10)(11)(12)16 ). Previously, we have shown, in the 3D density map, that the apoB protein component corresponds to the high-density regions and distributes on the edge of the particle ( 16 ).…”
Section: Overall Distribution Of Apobmentioning
confidence: 99%
“…Chatterton et al ( 8,9 ) pioneered studies to determine the distribution of apoB on the surface of LDL by employing the strategy of using paired monoclonal antibody (MAb) labeling to obtain projection images with negative stain electron microscopy followed by triangulation to determine the corresponding MAb locations. However, later work from several cryo-electron microscopy (cryo-EM) groups has shown that LDL is a discoidal-shaped particle at a temperature below the phase transition associated with the core-located cholesteryl esters (10)(11)(12)(13). Thus, the underlying assumption that LDL is a spherical particle limits the accuracy of the triangulation measurements.…”
mentioning
confidence: 99%
“…However, as reported in this issue of the Journal of Lipid Research , Liu et al ( 16 ) were successful in establishing an advanced fast freezing procedure to freeze LDL in a state above the phase transition. By doing so, they were able to capture an intermediate state in the transition from isotroHuman low density lipoprotein: the mystery of core lipid packing 1 pic to liquid-crystalline.…”
mentioning
confidence: 99%
“…Indeed, this patch nucleation behavior permits the temporary formation of local molecular microenvironments as suggested previously in terms of trigylceride segregation ( 17 ). Beyond detailed information on the internal core lipid organization, the paper by Liu et al ( 16 ) describes the direct impact of the core lipid phase transition on particle morphology and surface components. The fi ndings are consistent with earlier studies, which provided evidence that the physical state of the core lipids induces changes in the local molecular dynamics of the surface monolayer ( 18 , 19 ).…”
mentioning
confidence: 99%